Well Spacing Effects on Well Productivity in Coalbed Methane Reservoirs - Aji Wibowo Putro, Abdul Wahid (International Journal of Advanced Science and Technology, 2020)
Indonesia has large coalbed methane (CBM) reserves (453 TCF) and has the potential to supply domestic natural gas. One of the problems in producing gas from CBM is the amount of time that the dewatering process takes. The dewatering process involves draining water to reduce the pressure so that the methane gas can come out (as in Field X, Kalimantan). To accelerate the dewatering process, a well spacing method is used to determine the number of wells that will affect the cumulative gas production. A greater number of wells will increase CBM gas production but will also increase the cost and duration of production, so an economic analysis is needed to provide limits and determine the optimum yield. This paper will be conducted with a numerical simulator to discern the effects of well spacing on well productivity in CBM reservoirs. The result shows that models with 160 acres of well spacing have a recovery factor of 16,07%, 320 acres have a recovery factor of 11,5%, and 640 acres have a recovery factor of 5,82%. The result suggests that narrow spacing of wells causes greater cumulative gas production, but it plateaus (stabilizes) more quickly